Determining Whether Tai Chi Chuan Is Related to the Updating Function in Older Adults: Differences Between Practitioners and Controls - Yuan Yang; Tingting Chen; Chen Wang; Chen Wang; Ji Zhang; Ji Zhang; Xiaoxia Yuan; Xiaoxia Yuan; Xiaoke Zhong; Xiaoke Zhong; Shoufu Yan; Changhao Jiang; et al. (Frontiers Media S.A., 2022)
BackgroundTai Chi Chuan (TCC) is an effective method for delaying cognitive decline in older adults. However, in older adults, the association between long-term TCC practice and working memory updating has not been extensively studied.ObjectiveThis cross-sectional study investigated how updating function operationalized via Reaction Times (RTs) and Accuracy Rates (ARs) of N-Back tasks being measured in a laboratory setting is related to long term practice of TCC.MethodsTwenty-six healthy elderly people participated in this experiment. According to the duration of time TCC was practiced, 13 subjects in the TCC group had more than 5 years of experience with TCC exercise, and 13 elderly subjects who had not been systematically exposed to mind-body exercise were assigned to the control group. The N-back task was administered to every participant to evaluate the updating function.ResultsThe TCC group had faster RTs than the control group (p < 0.05). For the 1-back task, the TCC group showed faster RTs than the control group; for the 2-back task, the TCC group exhibited faster RTs than the control group. The TCC group had higher ARs than the control group (p < 0.05). For the 1-back task, the TCC group showed higher ARs than the control group; for the 2-back task, the TCC group exhibited higher ARs than the control group.ConclusionsLong-term TCC practitioners exhibit a better updating function as compared to controls who did not practice TCC. Thus, our findings suggest that long-term TCC positively influences the updating function of older adults, making it, in turn, an effective mind-body exercise to maintain specific aspects of cognitive functioning.